Educational Service Quality at Public Higher Educational Institutions: A Proposed Framework and Importance of the Sub-dimensions - Mohamad Yusof, Abdul Raheem; Hassan, Za’faran; Rahman, Sofiah Abdul; Ghouri, Arsalan Mujahid (International Journal of Economics, Business and Management Studies, 2012)
The objectives of this paper are to propose a conceptual framework for service quality in higher education from the perspective of the students, to identify the importance of the sub-dimensions and to determine whether there are differences between research universities and non-research universities. The sub-dimensions of Educational Service Quality according to this model are reliability, assurance, empathy, responsiveness, tangibles (program quality and services capes), communication, knowledge/ expertise, systems/secondary services, social responsibility and self-development. A survey instrument was used to gather information. The mean was used to determine the weighted importance of the sub-dimensions. ANOVA was used to determine if there are differences in importance of the sub-dimensions between research universities and nonresearch universities. In terms of importance, self-development and tangibles are most important, whereas empathy and assurance are least important. However there are methodological limitations as well as generalizability limitations which need some attention. The findings of this research may help academics and administrators allocate their resources. The use of a modified SERVQUAL instrument specifically designed for higher education.